Theoretical Comparison of Current Limiting Algorithms in Grid-Forming Inverter in Terms of Transient Stability - Dai Orihara; Hisao Taoka; Hiroshi Kikusato; Jun Hashimoto; Kenji Otani; Rahman Khaliqur; Taha Selim Ustun (IEEE Open Journal of Power Electronics)
Grid-forming (GFM) inverters enable inverter-based resources to act as voltage sources, providing support to power systems. They are anticipated to serve as a technology capable of replacing synchronous generators. However, during a fault, it is crucial to implement a function that limits their output current to prevent short circuit currents from exceeding their capacity. This raises concerns about the potential deterioration of transient stability in the power system. The influence of current limiting on transient stability depends on the current-limiting methodology. However, comprehensive theoretical evaluations are still lacking. This paper presents the theoretical evaluation of the influence of current limiting on transient stability for various current limitation algorithms. Accordingly, an equivalent virtual impedance (EVI) is proposed as a universal metric. EVI represents an impedance virtually assumed between the voltage source simulated in GFM control and the connection point of the inverter, and is computed so that the current through the EVI matches the limited output current. The transient stability is then assessed for various current-limiting algorithms based on the electric circuit characteristic of EVI. Finally, time-domain simulation is conducted to evaluate the consistency of the assessment.